Un modèle d’accompagnement de stagiaires en situation de handicap - Ruth Philion; Michelle Bourassa (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Quebec universities are experiencing a sharp increase in students with disabilities (SWD) which brings their internship supervisors under pressure in a teacher-training program. An exploratory study (Philion et al., 2019) suggests that emphasis should be placed on knowing how to accompany in a perspective of shared responsibility. Since this study, a research action examines this proposal. A learning community of researchers and supervisors co-constructs a reflective analysis framework called a concerted action plan oriented on the actions to be taken on both sides, which was used to support 27 trainees with disabilities (TWD). The resulting action plans were then analyzed and interpreted based on Bourassa's (2019) frame of reference. This frame suggests that a power relationship arises when an experienced person is responsible for supporting another. The frame of reference states that in a power relationship four variables interact: the trust to establish the bond, the right distance to co-construct meaning from what is happening, the requirement to pull the person up and the responsibility that falls to each part. Data analysis shows that the interactive combinations between these variables play a decisive role in the support offered to trainees. The conclusion is a supervision model combining a concerted supervisor/trainee action plan so that these trainees benefit from favorable conditions for their success.